Dampak Program Bantuan Sosial sebagai Intervensi Gizi Sensitif terhadap Status Stunting pada Balita - Sahara, Nasa Milta; Arianto, Dwini; Santoso, Mahar (UI Scholars Hub, 2024)
Stunting is a significant issue for nations, affecting both public health and economic development. It results from a combination of direct and indirect causes. The government addresses stunting through specific nutritional interventions targeting direct causes and sensitive nutritional interventions for indirect causes. Given the strong link between stunting and poverty, social assistance programs (BANSOS) such as the Family Hope Program (PKH) and Rice for the Poor (RASKIN) are crucial in combating stunting by improving socioeconomic conditions. This study analyzes the impact of these social assistance programs on stunting in children under five, using data from the 2007 and 2014 Indonesian Family Life Surveys (IFLS) and focusing on children aged 12-59 months. A logit model is employed to estimate the relationship between social assistance and stunting. Additionally, the study uses a combination of Propensity Score Matching (PSM) and Difference-in-Differences (DID) to evaluate the effects of these programs, ensuring comparability between groups by matching characteristics of recipients and non-recipients. The results of the PSM-DID analysis indicate that social assistance programs increase the likelihood of stunting by 4.8% (99% CI). These findings suggest that improvements in program design are necessary to ensure income effect effectively drive behavioral changes that help reduce stunting.